Addressing concerns and suggestions of blood donors: An assured way for donor motivation, recruitment, and retention - Sreethu Chand; R Amita; Debasish Gupta (Asian Journal of Transfusion Science, 2023)
The World Health Organization and National Blood Transfusion Council, Government of India, advocate regular repeat nonremunerated voluntary blood donors as the safest of all donors to meet the blood requirements of the country. Recruitment and retention of individuals as voluntary blood donors requires the adoption of novel and varied strategies protecting the voluntary nonremunerated nature of blood donation. In this review article, we are focusing on how addressing the donor suggestions and concerns has created a win–win situation for blood donors and blood transfusion services.